Vericiguat in patients with heart failure across the spectrum of left ventricular ejection fraction: a patient-level, pooled meta-analysis of VITALITY-HFpEF and VICTORIA - Chen, Chao; Lv, Jin; Liu, Changzhao (Frontiers in Endocrinology, 2024)
Vericiguat, the newest soluble guanylate cyclase (sGC) drug, is potentially beneficial in treating heart failure (HF). However, most studies have only confirmed the significant impact of sGC in patients with reduced left ventricular ejection fraction (LVEF). Therefore, the main objective of this meta-analysis was to comparatively analyze the effects of Vericiguat in the entire LVEF range based on previous studies. According to PubMed, Web of Science, Cochrane, and Embase databases, randomized controlled studies in the full LVEF stage range were screened, and two extensive clinical studies on Vericiguat, namely VICTORIA (LVEF<45%) and VITALITY-HFpEF (LVEF≥45%) were identified for analysis and systematic evaluation. We separately assessed the rates of primary outcomes, cardiovascular death, and serious adverse events in both studies. The results of our research confirmed that although the criteria for the primary outcome were not the same in the two extensive studies, it was evident that there was no difference in the primary outcome between the experimental Vericiguat group and the placebo group in the VITALITY-HFpEF (LVEF≥45%) (P=0.45), whereas the primary outcome of VICTORIA (LVEF<45%) was significantly improved with the administration of Vericiguat showing a significant improvement (RR 0.93; 95% CI 0.87 to 1.00), but the effect of Vericiguat on cardiovascular mortality was not significant across the full range of LVEF (RR 0.97; 95% CI 0.86 to 1.09), and the incidence of total serious adverse events did not differ significantly between the two studies (RR 0.96; 95% CI 0.89 to 1.03). Surprisingly, partial subgroups analysis of serious adverse events found that vericiguat treatment reduced the incidence of all-cause death, Cardiac disorders, Hypotension, and Hypertension in patients with LVEF<45%, with a particular effect on the incidence of Cardiac disorders. Taken together, Vericiguat had a significant benefit in HF patients with LVEF<45%, especially in patients with LVEF<24%; it had a less pronounced effect in HF patients with LVEF ≥45%, but no adverse effects were observed.